Dynamic Load Balancing in Multiple Gateway-based Industrial IoT-enabled WSNs - Mondal S.; Rawal A.P.; Chanak P. (My University, 2025)
The total digitization of the production process is one of the key goals of fourth industrial revolution to realize the interconnections of people, machines, and gadgets. The aggregation, reliable management of large amounts of data and dynamic reconfiguration of data links under spatio-temporal variation of data are vital aspects in Industrial Internet of Things (IIoT). Wireless Sensor Networks (WSNs) play a crucial role in this process. This paper proposes a load balancing scheme that effectively monitors wireless connections, dynamically reconfiguration under spatio-temporal variation of data. Furthermore, it also detects possible risks of channel saturation, and distributes data load among available nodes with minimizing the number of re-configurations, and total energy consumption. The experimental results show that the proposed scheme outperforms compared to state-of-the-art algorithms in terms of data received, packet loss, inter-gateway channel switching, average channel utilization for gateways. © 2024 IEEE.